Gestão por competências nos Institutos Federais de Educação do Nordeste brasileiro - Albuquerque, Márcio Oliveira (2018)
By Decree No. 5,707/2006, the management skills was incorporated into the brazilian federal public administration, being compulsory in source for the establishment of institutional guidelines for the development of functionalism federal public. Inserted in this context are the Federal Institutes of education, science and technology of the Brazilian Northeast, however, the implementation of this management model in these institutions comes meeting numerous challenges. The general objective of the study is to know the current reality of people management skills in Federal Education Institutes of northeastern Brazil, and from the experiences observed, present paths or strategies that can subsidize the exercise of this management. The research methodology was characterized as: applied, qualitative, descriptive and with multiple case studies. The unit of analysis was 6 (six) Federal Institutes of Education from northeastern Brazil, represented by their top leaders. The data collected through interview with these leaders were treated through content analysis. The results showed that: there is similarity in the fledgling State or embryonic exercise of people management skills in institutions; the bureaucratic structure and the cultural context of the institutions, the absence of more effective actions of the Ministry of education (MEC) and planning (MP), lack of exchange of experiences among institutions and the preparation of work teams to conduct the deployment process were some of the factors the process as facilitators factors singled out and realized that the leaders had trouble pointing them; and finally, the identification of these factors was able to indicate guidelines for the preparation of a guide for the favor of people management skills.